The Story of CD4+CD28− T Cells Revisited: Solved or Still Ongoing? - Kathrin Maly; Michael Schirmer (Journal of Immunology Research)
CD4+CD28− T cells are a unique type of proinflammatory T cells characterised by blockade of costimulatory CD28 receptor expression at the transcriptional level, which is still reversible by IL-12. In healthy individuals older than 65 years, these cells may accumulate to up to 50% of total CD4+ T lymphocytes as in many immune-mediated diseases, immunodeficiency, and specific infectious diseases. Here we focus on CD4+CD28− T cells in chronic immune-mediated diseases, summarizing various phenotypic and functional characteristics, which vary depending on the underlying disease, disease activity, and concurrent treatment. CD4+CD28− T cells present as effector/memory cells with increased replicative history and oligoclonality but reduced apoptosis. As an alternative costimulatory signal instead of CD28, not only natural killer cell receptors and Toll-like receptors, but also CD47, CTLA-4, OX40, and 4-1BB have to be considered. The proinflammatory and cytotoxic capacities of these cells indicate an involvement in progression and maintenance of chronic immune-mediated disease. So far it has been shown that treatment with TNF-α blockers, abatacept, statins, and polyclonal antilymphocyte globulins (ATG) mediates reduction of the CD4+CD28− T cell level. The clinical relevance of targeting CD4+CD28− T cells as a therapeutic option has not been examined so far.